PERANCANGAN SISTEM INFORMASI DESA BERBASIS WEB UNTUK PELAYANAN PUBLIK PADA DESA TENGKURAK, KECAMATAN TIRTAYASA, KABUPATEN SERANG - Amalia Khairunnisa Soemarsono, (2021)
Law No.6 of 2014 regarding Village Information Systems and Rural Area Development encourages village governments to develop village information systems for access to information for publics. The purpose of this research is to design and build a public service information system in Tengkurak Village, Tirtayasa District, Serang Regency. While the benefits of this research are to help the village government in providing Excellent service to the community and the community can access the system to get various information about the services provided by the Tengkurak Village Government. The method used in designing and building this village information system is the prototype method, while the database used is MySQL. The result of this research is a web-based village information system prototype.